How important are ICT and R&D investments for value added in the Swedish business sector? - Harald Edquist; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2015)
Since the mid-1990s value added has grown faster in the Swedish business sector than in the business sector of most other OECD countries. We investigate the association between ICT and R&D capital and value added in the Swedish non-farm business sector. By estimating neoclassical production function models on data for 47 different industries for the period 1993-2012 we show that ICT and R&D capital are significantly associated with value added for most specifications. When controlling for economic shocks the results show that on average, if ICT capital increases by 10 percent, value added increases by 1.8 percent. We also divide ICT capital into hardware and software capital. To our knowledge, this distinction has not been made in any previous study at the industry level. In this case only the estimated elasticity of software is significantly different from zero. One possible explanation could be that all industries invest in hardware, but only the ones that successfully invest in and implement software enjoy positive effects from ICT.
Keywords: O14; O32; O33; O47; 330; ICT; R&D; Industrial change; Panel data